Formulation of in-Vivo Experimental Model of Oral Submucous Fibrosis in Wistar Rat - Muhammad Umair Piracha, Iqra Ejaz, Saima Chaudhry, Sarah Ghafoor (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Oral submucous fibrosis is a chronic, fibrotic and crippling disease that affects the oral mucosa. It leads to progressive fibrosis that mainly involves the buccal mucosa but other parts of the oral cavity such as the tongue and palate can also be affected. There is a general consensus that areca nut and its constituents are mainly responsible for the pathogenesis of the disease. On histological examination of a biopsy taken from the human oral mucosa, OSMF presents with atrophic epithelium and juxta-epithelial deposition of a vast amount of collagen. Material and Methods:12 healthy male Wistar rats (age 5-6 weeks) were divided into two groups: group A (control) and group B (experimental) after ethical approval. Bleomycin is an anti-cancer drug that is used to create various animal models of fibrosis. In this study, bleomycin was injected into the buccal mucosa of Wistar rat at a concentration of 1mg/mL dissolved in 0.01 M phosphate-buffered saline (PBS) for 4-8 weeks daily. The control group was treated with normal saline. Body weight and mouth openings were recorded. A macroscopic examination was done along with a microscopic analysis of histopathological features and an immunohistochemical analysis of α-SMA expression. Masson’s trichrome stain was used to visualize the collagenous deposition in sub-epithelial tissue. Results: Clinically buccal mucosa showed lesions that mimicked OSMF. Changes in epithelium and lamina propria were observed in the experimental group as compared to the control group. At week 4, stratified squamous epithelium of buccal mucosa showed shortening of rete ridges and lamina propria showed deposition of thick separate collagen. At week 8, epithelium became flat, and atrophic with loss of rete ridges and lamina propria showed juxta-epithelial deposition of collagen which was completely hyalinized and α-SMA expression increased in myofibroblasts. Conclusion: The results from our study suggested that Wistar rats are a reproducible and sustainable model for OSMF. Keywords: Oral submucous fibrosis, animal model, bleomycin, fibrosis, alpha-smooth muscle actin.